2017
DOI: 10.2147/pgpm.s136341
|View full text |Cite
|
Sign up to set email alerts
|

<em>CYP2D6</em> phenotypes are associated with adverse outcomes related to opioid medications

Abstract: BackgroundVariation in the CYP2D6 gene may affect response to opioids in both poor and ultrarapid metabolizers, but data demonstrating such associations have been mixed, and the impact of variants on toxicity-related symptoms (e.g., nausea) is unclear. Therefore, we examined the association between CYP2D6 phenotype and poor pain control or other adverse symptoms related to the use of opioids in a sample of primary care patients.Materials and methodsWe identified all patients in the Mayo Clinic RIGHT Protocol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
1
24
1
Order By: Relevance
“…Our results are consistent with the results of previous research suggesting associations between CYP2D6 phenotypes and response to opioid use. 10 However, the proportion of individuals experiencing adverse reactions and poor pain control among those with CYP2D6 poor and ultra-rapid metabolizer phenotypes differed from the proportions reported by previous research. For example, VanderVaart et al 8 reported that 100% of CYP2D6 poor metabolizers experienced no analgesia, whereas 67% of ultra-rapid metabolizers reported adverse reactions.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Our results are consistent with the results of previous research suggesting associations between CYP2D6 phenotypes and response to opioid use. 10 However, the proportion of individuals experiencing adverse reactions and poor pain control among those with CYP2D6 poor and ultra-rapid metabolizer phenotypes differed from the proportions reported by previous research. For example, VanderVaart et al 8 reported that 100% of CYP2D6 poor metabolizers experienced no analgesia, whereas 67% of ultra-rapid metabolizers reported adverse reactions.…”
Section: Discussioncontrasting
confidence: 57%
“…To address differences in CYP2D6 classification between studies, we also investigated associations between CYP2D6 activity scores and response to opioids, and found that these associations corroborated the results using CYP2D6 phenotype categorizations reported in the current study and in previous research. 8,10 However, we note that higher CYP2D6 activity scores were not significantly associated with adverse reactions or poor pain control. Despite our large sample size, the relatively small number of outcomes may have resulted in an inability to detect a statistically significant association.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations